Phylogeographical history of the white seabream Diplodus sargus (Sparidae): Implications for insularity - Gonzalez-Wangueemert, Mercedes (2016)
Partial sequences of the mitochondrial control region and its comparison with previously published cytochrome b (cyt-b) and microsatellite data were used to investigate the influence of island isolation and connectivity on white seabream genetic structure. To achieve this, a total of 188 individuals from four island localities (Castellamare and Mallorca, Mediterranean Sea; Azores and Canary Islands, Atlantic Ocean) and five coastal localities (Banyuls, Murcia and Tunisia, Mediterranean Sea; Galicia and Faro, Atlantic Ocean) were analysed. Results showed high haplotype diversity and low to moderate nucleotide diversity in all populations (except for the Canary Islands). This pattern of genetic diversity is attributed to a recent population expansion which is corroborated by other results such as cyt-b network and demographic analyses. Low differentiation among Mediterranean/Atlantic and coastal/island groups was shown by the AMOVA and FST values, although a weak phylogeographic break was detected using cyt-b data. However, we found a clear and significant island/ distance effect with regard to the Azores islands. Significant genetic differentiation has been detected between the Azores islands and all other populations. The large geographical distance between the European continental slope and the Azores islands is a barrier to gene flow within this region and historic events such as glaciation could also explain this genetic differentiation.